Lists, lists and more lists; Listas, listas y más listas - Cussen-Abud, F (Universidad de la Serena,Departamento de Artes y Letras, 2025)
This article consists of three parts. In the first, we present the category of list based on Umberto Eco’s distinction (practical versus poetic) and its function in ancient literature and in Modernity is studied, through the practice of taking notes (excerpta) in formats such as the portfolio and the collect. Second, we comment on a variety of contemporary practices based on the list, already legitimized as a literary and artistic practice. In the third section we focus on a specific model, the “I remember”, created by Joe Brainard and popularized by Georges Perec, which has given rise to numerous versions and variations. © (2025), (Este trabajo se encuentra bajo la licencia Creative Commons Attribution 4.0). All rights reserved.